The ideological dimension in the stories of the first issue of the magazine Narracion (1966) - Ramos Badillo, Víctor (2021)
In the following article, the stories that make up the first issue of Narración magazine (1966) will be analyzed in order to visualize the ideological problematizations that it brings about the Marxist criticism assumed by the members of the magazine. Although the Narración group highlighted a political-vindictive movement from the underprivileged class in the pages of the journal, in the section destined to fiction, the published stories manifest different narrative tendencies that are not limited to posing a mechanical representation of the class struggle, but a different location of class conflict and also its symbolic or political implications. For this objective, the concept of ideology applied to the literary form will be used, which will allow to establish the limits and contradictions that subsist in the narrative process of the story.